Sistem Informasi Administrasi Pada Lembaga Kursus Dengan Metodologi Berorientasi Obyek Studi Kasus: Nurul Fikri English Course - Anita Diana; Endriyanto Endriyanto (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2013)
Computerized data processing is needed by every educational institution to achieve the optimal efficiency and optimal employment. Such as in educational institutions Nurul Fikri English Course, data processing are still done manually. Therefor effective and efficient are difficult to achieve in the institutions. Administrative processes such as student data are still recorded manually on the form, and it will make the search of student data requires considerable tima, and reporting was not effective and efficient. So it requires a computerized system that can handle the problems. Application system that will be implemented, will using object-oriented methodology approach Object-oriented methodology is trusted more flexible and more easily when there is a change in the program, object Oriented program is more widely used in software engineering on a large scale, and acknowledge that OOP is easier to learn, both for novice than previous methods, and OOP approach is easier to develop and to maintain. With computerized system makes the recording data much easier and the process administration of the students is smoother. In addition it facilitates the process of printing report based on a desired period so it can find information easily and quickly and employee performance more effectively and efficintly. The system is made through Microsoft Visual Studio 2005 application with Microsoft Access 2003 database.Keywords: Administration, Course, Object Oriented